Ethno-Techno-Science Pedagogy in Islamic Primary Schools: A Systematic Review of Indonesia's Merdeka Curriculum Implementation and Science Literacy Outcomes - Khalimatus Sa’diyah; Karno Karno (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2026)
This systematic review evaluates the implementation of the Merdeka Curriculum in Madrasah Ibtidaiyah (Islamic primary schools), focusing on the integration of ethno-techno-science approaches into science pedagogy. Following Cochrane methodology, six structured queries were run across Semantic Scholar, PubMed, OpenAlex, arXiv, and clinical trial databases. From 164 initial records, 23 studies met inclusion criteria after deduplication, screening, and full-text assessment. Risk of bias was assessed using adapted Cochrane tools, and GRADE was used to evaluate certainty of evidence. The findings show that implementation employs project-based learning and differentiated instruction, unifying natural and social sciences into the IPAS subject. Ethnoscience integration occurs through traditional biotechnology products, local agricultural practices, and cultural artifacts. Key barriers include insufficient teacher understanding (40% unprepared), limited infrastructure, and scarce training opportunities. One quasi-experimental study reported moderate improvement in science literacy (N-Gain = 0.46) after culture-based instruction. GRADE certainty ranged from very low to moderate across outcomes. The review concludes that while ethnoscience-integrated Merdeka Curriculum implementation is feasible and potentially beneficial for science literacy, evidence remains limited by qualitative designs and small sample sizes. Strengthening teacher capacity and infrastructure is critical for successful implementation.